Analysis of the Effect of Corporate Social Responsibility and Good Corporate Governance on Stock Performance in Public Companies in Indonesia - Loso Judijanto; Muhamad Akbar; Deni Iskandar; Eko Sudarmanto; Himawan Sutanto (Westscience Press, 2024)
This study analyzes the effect of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) on Stock Performance (SP) in public companies in Indonesia. Using a sample of 160 companies and a quantitative approach, data was collected through a 5-point Likert scale survey and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS 3). The findings reveal that both CSR and GCG positively influence stock performance, with GCG having a stronger impact (β = 0.612) compared to CSR (β = 0.384). The results emphasize the importance of ethical practices and effective governance in enhancing investor confidence and improving stock market performance. These findings provide important implications for managers, investors, and policymakers, suggesting that companies focusing on CSR and GCG are likely to experience better financial outcomes in the stock market.